IMPLEMENTASI KARUNIA BERKATA-KATA DENGAN HIKMAT DI GEREJA BETH-EL TABERNAKEL SILOAM PANGLEON - Ka'ka', Herliyanti Anton; Kristiawan, Ragil; Jahja, Soendoro (STT Kristus Alfa Omega, 2024)
This study aims to find out how much the congregation has implemented the gift of speaking with wisdom at Beth-el Tabernacle Siloam Pangleon Church. This study used a quantitative method by collecting data using a questionnaire. Based on the results of the hypothesis testing carried out in this study, with an empirical calculation of 100%, the researcher found that the congregation’s implementation of the gift of speaking with wisdom at Beth-el Tabernacle Siloam Pangleon Church was ini the very good category, namely 88%.